A New Approach to Atopic Dermatitis Control with Low-Concentration Propolis-Loaded Cold Cream - Bianca Aparecida Martin; Camila Nunes Lemos; Luciana Facco Dalmolin; Caroline Arruda; Íris Sperchi Camilo Brait; Maurílio de Souza Cazarim; Estael Luzia Coelho da Cruz-Cazarim; Paula Carolina Pires Bueno; Maurílio Polizello Júnior; Leonardo Régis Leira Pereira; Renata Nahas Cardili; Renata Fonseca Vianna Lopez (MDPI AG, 2021)
Atopic dermatitis (AD) is a chronic inflammatory skin disease that is difficult to treat. Traditional cold cream, a water-in-oil emulsion made from beeswax, is used to alleviate AD symptoms in clinical practice, although its effectiveness has not been scientifically proven. The addition of propolis has the potential to impart anti-inflammatory properties to cold cream. However, in high concentrations, propolis can trigger allergic reactions. Thus, the objective of this work was to develop a cold cream formulation based on purified beeswax containing the same amount of green propolis present in raw beeswax. The impact of adding this low propolis concentration to cold cream on AD control was evaluated in patients compared to cold cream without added propolis (CBlank). Raw beeswax was chemically characterized to define the propolis concentration added to the propolis-loaded cold cream (CPropolis). The creams were characterized as to their physicochemical, mechanical, and rheological characteristics. The effect of CPropolis and CBlank on the quality of life, disease severity, and skin hydration of patients with AD was evaluated in a triple-blind randomized preclinical study. Concentrations of 34 to 120 ng/mL of green propolis extract reduced TNF-α levels in LPS-stimulated macrophage culture. The addition of propolis to cold cream did not change the cream's rheological, mechanical, or bioadhesive properties. The preclinical study suggested that both creams improved the patient's quality of life. Furthermore, the use of CPropolis decreased the disease severity compared to CBlank.